Image block encryption algorithm based on chaotic maps. Issue 1 (1st February 2018) - Liu, Lingfeng; Hao, Shidi; Lin, Jun; Wang, Ze; Hu, Xinyi; Miao, Suoxia
Abstract : Advanced in unpredictability, ergodicity and sensitivity to initial conditions and parameters, chaotic maps are widely used in modern image encryption algorithms. In this study, the authors propose a novel image block encryption algorithm based on several widely used chaotic maps. In their algorithm, the image blocking method is variable, and both shuffling and substitution algorithms are adopted based on different chaotic maps. Several simulations are provided to evaluate the performances of this encryption scheme. The results demonstrate that the proposed algorithm is with high security level and fast encryption speed, which can be competitive with some other recently proposed image encryption algorithms.